The Improvement of Eye Hand Foot Score of Disability through Empowerment Education, Home-Based Self Care, Peer Support - Taufan Arif (Journal of Ners and Midwifery, 2020)
Introduction: Mycobacterium leprae infiltration results in inflammation of the nerves. This condition results in a progressive decline of nerve function of the eyes, hands and feet. The main burden of people with leprosy is a disability that will affect all aspects of their lives. The objective of this study was to explain the effect of empowerment education, home-based self care, and peer support for disability. Methods: True experimental randomized pre-post test control group design. The sampling technique used simple random sampling consisted 16 respondents. The independent variable was empowerment education, home-based self care, and peer support. The dependent variable was disability. The data were collected by in-vivo biological observation sheets. The data were analyzed by Mann-Whitney Test and Wilcoxon Signed test. Results: The result showed that there was an effect of intervention on disability with Wilcoxon Sign Rank Test 0.046. Discussion: Empowerment education interventions, home-based self care, peer support increase the knowledge of leprosy clients in self care. The key to disability prevention is 3M, which is checking, protecting, and caring for the eyes, hands and feet. These three interventions will increase patient confidence in self-care at home. The support of peers will also make it easier for clients to weigh the advantages and disadvantages when not complying with comprehensive treatment.